Eficácia do tratamento biológico em gotejadores operando com água residuária doméstica tratada - Costa, Danniely de Oliveira (2014)
Water scarcity and environmental degradation in semiarid region are factors that increase the use of treated domestic wastewater aiming its agricultural use. The drip irrigation becomes more sustainable method for this purpose, due to high application efficiency and low risk of contamination of agricultural produce and operators in the field. However, they have a high susceptibility of obstruction the emitters, particularly when operating with wastewaters, because of the biofouling's formation. In this context, the present study seeked to employ biological treatment aimed at the drippers' unblocking that operate with treated domestic wastewater. For that, we assembled an experimental bench in the Experimental Unit for Water Reuse (EUWR), which has a total area of 793.13 m2, installed on the Zoo and Botanical Park located at the Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró campus. To assessment of hydraulic performance and clogging of three types of drippers applying wastewater treated for 400 h, was mounted an experiment with four irrigation units, equipped with three types of emitters (G1, G2 and G3), with three replicates (three lateral lines by type of dripper). Every 80 h of operation evaluated the CUC, CUD, Us, CVQ, RQR and Q. After the operation time of 400 h, was held the second experiment, characterized by the use of biological treatment that consisted of catalyst enzymatic brand Byosol Swift, line FA (Aseptic Fosse) and powder concentrate of bacteria MaxBio brand, used together . The experiment was mounted with three factors, being the first factor the three types of emitters, the second factor the three treatments T1 (without application of the product), T2 (first application of the product) and T3 (second application of the product) and the third factor the dosages DOS1 (80 mg L-1), DOS2 (160 mg L-1), DOS3 (240 mg L-1) and DOS4 (320 mg L-1) the product MaxBio in three replicates (three lateral lines by type of dripper in each irrigation unit). The data were submitted to analysis of simple and multiple regression, mean test and parametric Pearson correlations test. The results indicated that the formation of biofouling resulting from the interaction between the physical, chemical and biological agents led to partial and total clogging of emitters and hence reduction in the hydraulic performance of irrigation units which operate with domestic wastewater treated. The dripper G1 was more susceptible to clogging than the drippers G2 and G3. In dripper G1, the dosage of 80 mg L-1 MaxBio showed more positive results, as the recovery of hydraulic performance, this being more expressive effect with the completion of the second application of the product. A dosage of 80 mg L-1 MaxBio also showed the best results in clearing the dripper G3, the first application of the product is required, only